The Allergic Rhinitis and its Impact on Asthma (ARIA) score of allergic rhinitis using mobile technology correlates with quality of life: The MASK study. Issue 2 (5th October 2017) - Bousquet, J.; Arnavielhe, S.; Bedbrook, A.; Fonseca, J.; Morais Almeida, M.; Todo Bom, A.; Annesi‐Maesano, I.; Caimmi, D.; Demoly, P.; Devillier, P.; Siroux, V.; Menditto, E.; et al.
Abstract: Mobile technology has been used to appraise allergic rhinitis control, but more data are needed. To better assess the importance of mobile technologies in rhinitis control, the ARIA (Allergic Rhinitis and its Impact on Asthma) score ranging from 0 to 4 of the Allergy Diary was compared with EQ‐5D (EuroQuol) and WPAI‐AS (Work Productivity and Activity Impairment in allergy) in 1288 users in 18 countries. This study showed that quality‐of‐life data (EQ‐5D visual analogue scale and WPA‐IS Question 9) are similar in users without rhinitis and in those with mild rhinitis (scores 0‐2). Users with a score of 3 or 4 had a significant impairment in quality‐of‐life questionnaires.